Densification and Combustion of Cherry Stones - Magdalena Dołżyńska; Sławomir Obidziński; Małgorzata Kowczyk-Sadowy; Małgorzata Krasowska (Energies, 2019)
The aim of the presented research was to determine the suitability of cherry stones as a solid fuel. Mixtures of cherry stones with the addition of 10%, 15%, and 20% rye bran as a binder were subjected to the pressure agglomeration process in a rotary matrix working system (170, 220, and 270 rpm). The density of pellets, their kinetic durability, and power demand of the granulator’s device for each mix were determined. The highest quality was characterized by pellets containing 20% rye bran, which were combusted in a 25 kW boiler with a retort grate. The concentration of CO, CO2, NO, SO2, HCl, and O2 in the exhaust gas was tested. On the basis of the results of combustion, high heating value (HHV), low heating value (LHV), and elemental analysis, it was found that pellets from cherry stones with the addition of rye bran can serve as a substitute for wood pellets in low-power installations.